Epidemiological and molecular investigation of a measles outbreak in Punjab, Pakistan, 2013‐2015. Issue 8 (25th May 2018) - Zaidi, Syed Sohail Zahoor; Hameed, Abdul; Ali, Naeem; Rana, Muhammad Suleman; Umair, Massab; Alam, Muhammad Masroor; Aamir, Uzma Bashir; Khurshid, Adnan; Sharif, Salmaan; Shaukat, Shahzad; Angez, Mehar; Mujtaba, Ghulam; et al.
Abstract : Despite the availability of an effective vaccine, the measles virus continues to cause significant morbidity and mortality in children worldwide. Molecular characterization of wild‐type measles strains is an invaluable component of epidemiological studies or surveillance systems that provides important information pertinent to outbreak linkages and transmission pathways. Serum samples and throat swabs were collected from suspected measles cases from the Punjab province of Pakistan (2013‐2015) and further tested for measles immunoglobulin M (IgM) through enzyme‐linked immunosorbent assay and reverse‐transcriptase polymerase chain reaction for molecular characterization. Among the total of 5415 blood samples, 59% tested positive for measles IgM. Males had a higher infection rate (55%) than females (45%), and the highest frequency of positive cases (63%) was found in the age group of 0 to 5 years. Partial sequencing of the nucleoprotein gene showed that 27 strains belonged to the B3 genotype, whereas 2 viruses were identified as D4. On phylogenetic analysis, Pakistani B3 strains were found to be closely related to previously reported indigenous strains and those from neighboring countries of Iran and Qatar. This is the first report on the detection of the measles B3 genotype from Punjab, Pakistan. The current study shows a high burden of measles infections in Punjab province owing to poor routine immunization coverage in major cities. It is imperative that national health authorities adopt strategic steps on an urgent basis for improvement of routine immunization coverage. Molecular epidemiology of the measles viruses circulating in different parts of the country can provide useful data to manage future outbreaks.